MODEL PENGEMBANGAN KREATIVITAS DAN INOVASI DALAM ERA EKONOMI DIGITAL (STUDI KASUS L.FASHION.ID) - Lia, Neneng; Agung, Syahrum; Megawati, Dewi (Jurnal Pijar, 2024)
The development of the business world demands effective human resource management. However, the high unemployment rate in Indonesia highlights the need to foster creativity and innovation to create new job opportunities, especially in the digital economy era, which enables promising online business opportunities. The purpose of this research is to understand how planning models for the development of creativity and innovation can be applied in the digital economy era. The research method used is descriptive quantitative research. The population in this study consists of actors in L.Fashion.Id (resellers and customers), totaling 78 individuals. Data analysis was conducted using multiple linear regression analysis. The results of the study indicate that creativity and innovation have a significant impact on the digital economy. Additionally, the digital economy in L.Fashion.Id has increased sales volume over the past three years.